Process for the preparation of a sulfide electrolyte powder and a process for the shaping thereof

CN122996528APending Publication Date: 2026-10-27GUANGDONG HENGQIN YANPO ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202680002730.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

另外,目前通过单一的研磨方式很难获取粒径分布均匀的固态电解质粒料

Benefits of technology

[0023]在本申请中,通过特定配比的原料先后经过特定参数的球磨处理、特定参数的砂磨处理、分离和特定温度的干燥处理后,能够提高硫化物电解质粉末的粒径均匀性。另外,本申请的电解质粉末的制备过程的处理温度低于100℃,并且主要采用砂磨、球磨、分离和干燥处理,工艺过程简单,相比于高温烧结法的能耗低,并且不存在溶剂回收的问题。因此本申请的制备方法还利于降低生产成本、提高生产效率以及利于提高环境友好性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996528A_ABST
    Figure CN122996528A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a sulfide electrolyte powder, comprising the following steps: weighing raw materials according to a proportion, wherein the raw materials comprise a sulfide material and lithium halide, the amount of the lithium halide is 0.5-5 mol% of the total amount of the sulfide material and the lithium halide; the weighed raw materials are placed in a ball mill tank under the protection of an inert atmosphere to perform ball milling, the ball milling time is 2-4 hours, and the ball milling speed is 300-400 r / min; the pretreated powder is placed in a sand milling device under the protection of an argon atmosphere to perform sand milling, the sand milling time is 2-4 hours, the sand milling temperature is controlled below 25 DEG C, and the sand milling linear speed is 11-13 m / s; and the sand milling slurry is subjected to separation and drying operations, the drying temperature is 50-60 DEG C, and the drying time is 8-12 hours. The application further provides a forming method of the sulfide electrolyte powder, and the preparation method can improve the particle size uniformity of the sulfide electrolyte powder, is beneficial to reducing production cost, improving production efficiency and improving environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of electrolytes, and specifically to a method for preparing sulfide electrolyte powder and its molding method. Background Technology

[0002] The inhomogeneity of solid electrolyte particles can affect the capacity and safety of solid-state batteries. Currently, common methods for preparing sulfide electrolyte powders mainly include high-temperature sintering, solution processing, and mechanical alloying. High-temperature sintering requires a high-temperature environment, is complex, and consumes a lot of energy. Solution processing requires organic solvents, is cumbersome, and solvent recovery is difficult, affecting production efficiency and environmental friendliness. Mechanical alloying easily introduces impurities during the preparation process. Furthermore, it is currently difficult to obtain solid electrolyte particles with uniform particle size distribution using only grinding methods. Summary of the Invention

[0003] In order to overcome the shortcomings of the prior art, the present invention aims to provide a method for preparing sulfide electrolyte powder. By coordinating the parameters of each step of the preparation method, the particle size uniformity of the sulfide electrolyte powder can be improved. In addition, the preparation method is conducive to reducing production costs, improving production efficiency, and improving environmental friendliness.

[0004] In addition, this application also provides a method for molding sulfide electrolyte powder, which also helps to reduce production costs and improve environmental friendliness.

[0005] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0006] A method for preparing a sulfide electrolyte powder includes the following steps:

[0007] Weigh the raw materials according to the formula, the raw materials include sulfide materials and lithium halides, and the amount of lithium halides is 0.5-5 mol% of the total amount of the sulfide materials and the lithium halides.

[0008] The weighed raw material is placed in a ball mill jar under an inert atmosphere and ball milled to obtain pretreated powder. The ball milling time is 2-4 hours and the ball milling speed is 300-400 r / min.

[0009] The pretreated powder is placed in a sand mill under an argon atmosphere for sand milling to obtain a sand mill slurry. The sand milling time is 2-4 hours, the sand milling temperature is controlled below 25℃, and the sand milling linear speed is 11-13m / s.

[0010] The sand-milled slurry is separated and dried to obtain electrolyte powder. The drying temperature is 50-60℃ and the drying time is 8-12 hours.

[0011] In some possible embodiments, the sulfide material is Li6PS5Cl, and the amount of lithium halide is 0.5 mol% of the total amount of the sulfide material and the lithium halide.

[0012] In some possible embodiments, the lithium halide is selected from LiCl.

[0013] In some possible embodiments, the sulfide material is a mixture of Li2S and P2S5, wherein the molar ratio of Li2S to P2S5 is 3:1, and the amount of lithium halide is 5 mol% of the total amount of the sulfide material and the lithium halide.

[0014] In some possible embodiments, the lithium halide is selected from LiI.

[0015] In some possible embodiments, the grinding temperature is controlled below 20°C.

[0016] In some possible embodiments, the ball milling media are zirconia balls with a diameter of 5-10 mm, and the sand milling media are zirconia beads with a diameter of 0.3-0.8 mm.

[0017] In some possible embodiments, the purity of the sulfide material is greater than or equal to 99.9%.

[0018] This application also provides a method for forming sulfide electrolyte powder, which uses sulfide electrolyte powder obtained by the preparation method described above as raw material, and prepares the electrolyte powder into a film or sheet by cold isostatic pressing to obtain a sulfide electrolyte profile. The pressure of cold isostatic pressing is 550-650 MPa, and the holding time is 10-15 minutes.

[0019] In some possible embodiments, the steps further include:

[0020] The sulfide electrolyte profile is subjected to low-temperature sintering at a temperature of 200-250°C for 1-2 hours.

[0021] The sintered profiles are then annealed at a temperature of 100-150℃ for 1-2 hours.

[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0023] In this application, by sequentially subjecting raw materials in a specific ratio to ball milling, sand milling, separation, and drying at a specific temperature using specific parameters, the particle size uniformity of the sulfide electrolyte powder can be improved. Furthermore, the preparation process of the electrolyte powder in this application operates at temperatures below 100°C and primarily employs sand milling, ball milling, separation, and drying. This process is simple, consumes less energy compared to high-temperature sintering, and eliminates the issue of solvent recovery. Therefore, the preparation method of this application also helps reduce production costs, improve production efficiency, and enhance environmental friendliness.

[0024] In addition, the molding method of the sulfide electrolyte powder provided in this application does not require high-temperature sintering or reagent recovery, which helps to reduce production costs and improve environmental friendliness.

[0025] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments. Attached Figure Description

[0026] Figure 1 A flowchart of a method for preparing sulfide electrolyte powder is provided for one embodiment of this application;

[0027] Figure 2 The particle size distribution diagram of the electrolyte powder provided in Example 1;

[0028] Figure 3 The particle size distribution diagram of the electrolyte powder provided in Example 2. Detailed Implementation

[0029] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0031] The following describes some embodiments of the present invention in detail. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0032] Reference Figure 1 This application provides a method for preparing sulfide electrolyte powder, the method comprising the following steps.

[0033] Step S101: Weigh the raw materials according to the specified ratio. The raw materials include sulfide materials and lithium halides, and the amount of lithium halides used is 0.5-5 mol% of the total amount of the sulfide materials and lithium halides. For example, lithium halides may include one of LiI and LiCl. The sulfide materials may consist of one sulfide or a mixture of several sulfides.

[0034] Step S102: The weighed raw material is placed in a ball mill jar under an inert atmosphere and ball milled to obtain a pretreated powder. The ball milling time is 2-4 hours, and the ball milling speed is 300-400 r / min. For example, the inert atmosphere may include either argon or helium.

[0035] Step S103: The pretreated powder is placed in a sand mill under an argon atmosphere for sand milling to obtain a sand mill slurry. The sand milling time is 2-4 hours, the sand milling temperature is controlled below 25℃, and the sand milling linear speed is 11-13 m / s. Preferably, the sand milling temperature is controlled between 15℃ and 25℃.

[0036] Step S104 involves separating and drying the milled slurry to obtain electrolyte powder. The drying temperature is 50-60℃, and the drying time is 8-12 hours. For example, filtration or centrifugation can be used for separation; for example, a 500-800 mesh filter screen can be used for filtration.

[0037] In this application, by sequentially subjecting raw materials in a specific ratio to ball milling, sand milling, separation, and drying at a specific temperature using specific parameters, the particle size uniformity of the sulfide electrolyte powder can be improved. Furthermore, the preparation process of the electrolyte powder in this application operates at temperatures below 100°C and primarily employs sand milling, ball milling, separation, and drying. This process is simple, consumes less energy compared to high-temperature sintering, and eliminates the issue of solvent recovery. Therefore, the preparation method of this application also helps reduce production costs, improve production efficiency, and enhance environmental friendliness.

[0038] In some embodiments, the sulfide material is Li6PS5Cl, and the amount of lithium halide is 0.5 mol% of the total amount of the sulfide material and the lithium halide. Preferably, the lithium halide is LiCl. Preferably, the milling temperature is controlled below 25°C. Preferably, the milling temperature is controlled between 15°C and 25°C.

[0039] In some embodiments, the sulfide material is a mixture of Li₂S and P₂S₅, wherein the molar ratio of Li₂S to P₂S₅ is 3:1, and the amount of lithium halide is 5 mol% of the total amount of the sulfide material and the lithium halide. Preferably, the lithium halide is LiI. Preferably, the milling temperature is controlled below 20°C. Preferably, the milling temperature is controlled between 15°C and 20°C.

[0040] In some embodiments, the ball milling media are zirconia balls with a diameter of 5-10 mm, and the sand milling media are zirconia beads with a diameter of 0.3-0.8 mm. Optimization of the parameters of the ball milling media and the sand milling media facilitates mild and efficient pretreatment and better matches the characteristics of the sulfide electrolyte raw material.

[0041] In some embodiments, the purity of the sulfide material is greater than or equal to 99.9%.

[0042] This application also provides a method for molding sulfide electrolyte powder, using sulfide electrolyte powder obtained by any of the above preparation methods as raw material, and preparing the electrolyte powder into a film or sheet by cold isostatic pressing to obtain a sulfide electrolyte profile. The cold isostatic pressing pressure is 550-650 MPa, and the holding time is 10-15 minutes. Preferably, the cold isostatic pressing pressure is 580-600 MPa. Similarly, the molding method of sulfide electrolyte powder does not require high-temperature sintering or reagent recovery, thus helping to reduce production costs and improve environmental friendliness.

[0043] In some embodiments, the molding method further includes the steps of: sintering the sulfide electrolyte profile at a low temperature of 200-250°C for 1-2 hours; and annealing the sintered profile at 100-150°C for 1-2 hours. The low-temperature sintering and annealing steps can improve the mechanical strength and ionic conductivity of the sulfide electrolyte profile.

[0044] The following detailed description uses specific examples.

[0045] Example 1

[0046] 1. Raw Material Preparation: Li₂S (CAS No. 12136-58-2, Hangzhou Kaiyada Semiconductor Materials Co., Ltd., purity 99.9%) and P₂S₅ (CAS No. 1314-80-3, purity 99.9%, Hubei Shengwei New Materials Co., Ltd.) were selected as sulfide materials, and LiI (CAS No. 10377-51-2, purity 99.9%, Bailingwei Technology) was selected as a dopant. The raw materials were weighed according to the molar ratio of Li₂S:P₂S₅:LiI of 71.25:23.75:5. The amount of LiI used was 5% of the total molar amount of LiI, Li₂S, and P₂S₅, that is, the amount of lithium halide was 5 mol% of the total amount of the sulfide material (a mixture of Li₂S and P₂S₅) and the lithium halide. The molar ratio of Li₂S:P₂S₅ was 3:1.

[0047] 2. Pretreatment: Weighed Li₂S, P₂S₅, and LiI raw materials were placed in a ball mill jar under argon (inert atmosphere) protection for ball milling pretreatment to obtain pretreated powder. The ball milling time was 4 hours, the ball milling speed was 300 r / min, and the ball milling media was zirconia balls.

[0048] 3. Sand milling preparation: The pretreated powder is placed in a fully closed-loop sand milling device and sand milled under argon atmosphere protection to obtain sand milling slurry. The sand milling time is 2 hours, the sand milling medium is zirconia beads with a diameter of 0.3 mm, the sand milling temperature is controlled below 20℃ (between 15℃ and 20℃), and the sand milling linear speed is 13 m / s.

[0049] 4. Powder Collection: After sand milling, the milled slurry is filtered (using a 500-mesh sieve) and dried to obtain uniform and fine sulfide electrolyte powder. The drying temperature is 50℃, and the drying time is 12 hours. The particle size distribution of the electrolyte powder obtained in Example 1 is as follows: Figure 2 As shown.

[0050] 5. Electrolyte powder forming process: The dried sulfide electrolyte powder is prepared into electrolyte sheets or films of the required shape by cold isostatic pressing, resulting in sulfide electrolyte profiles. The cold isostatic pressing pressure is 600 MPa and the holding time is 10 minutes.

[0051] 6. Post-treatment: The sulfide electrolyte profile undergoes post-treatment, including low-temperature sintering and annealing after sintering. The sintering temperature is 200℃, and the sintering time is 2 hours. The annealing temperature is 100℃, and the annealing time is 1 hour. The flexural strength of the sulfide electrolyte profile obtained in this embodiment is 85±5MPa, and the ionic conductivity is 2.1×10⁻⁶. -3 S / cm.

[0052] Example 2

[0053] 1. Raw Material Preparation: Li6PS5Cl (Sichuan Liuzu Semiconductor Materials Co., Ltd., with a purity greater than or equal to 99.9%, corresponding to a purity of 99.95%) was selected as the sulfide material, and LiCl (CAS number 7447-41-8, Merck Life Sciences, with a purity of ≥99.98%) was selected as the dopant. The raw materials were weighed according to the molar ratio of Li6PS5Cl to LiCl of 99.5:0.5. The amount of lithium halide used was 0.5 mol% of the total amount of the sulfide material and the lithium halide.

[0054] 2. Pretreatment: The weighed Li6PS5Cl and LiCl raw materials are placed in a ball mill jar under an inert gas atmosphere (argon) for ball milling pretreatment to obtain pretreated powder. The ball milling time is 2 hours, the rotation speed is 400 r / min, and the ball milling media is zirconia balls.

[0055] 3. Sand milling preparation: The pretreated powder is placed in a fully closed-loop sand milling device and sand milled under argon atmosphere protection to obtain sand milling slurry. The sand milling time is 4 hours, the sand milling media is zirconia balls with a diameter of 0.8 mm, the sand milling temperature is controlled below 25 degrees (between 15℃ and 25℃), and the linear velocity is 11 m / s.

[0056] 4. Powder Collection: After sand milling, the milled slurry is filtered (using an 800-mesh sieve) and dried to obtain uniform and fine sulfide electrolyte powder. The drying temperature is 60℃, and the drying time is 8 hours. The particle size distribution of the electrolyte powder obtained in Example 1 is as follows: Figure 3 As shown.

[0057] 5. Electrolyte powder forming process: The dried sulfide electrolyte powder is prepared into electrolyte sheets or films of the required shape by cold isostatic pressing, resulting in sulfide electrolyte profiles. The cold isostatic pressing pressure is 600 MPa and the holding time is 15 minutes.

[0058] 6. Post-treatment: The obtained sulfide electrolyte profiles undergo post-treatment, which includes low-temperature sintering and annealing after low-temperature sintering. The sintering temperature is 250℃ and the sintering time is 1 hour. The annealing temperature is 150℃ and the annealing time is 2 hours.

[0059] The flexural strength of the sulfide electrolyte profile obtained in this embodiment is 92±6 MPa, and the ionic conductivity is 2.5×10⁻⁶ MPa. - 3 S / cm.

[0060] Example 3

[0061] The difference from Example 1 is that no post-processing steps are performed, i.e., no low-temperature sintering and annealing steps are performed. The flexural strength of the sulfide electrolyte profile obtained in this example is 70±5 MPa, and the ionic conductivity is 1.8×10⁻⁶. -3 S / cm.

[0062] The performance tests of the above embodiments were conducted in accordance with the following test standards.

[0063] Particle size distribution test: The test was conducted in accordance with the national standard GB / T 19077-2016 "Particle size analysis by laser diffraction".

[0064] Mechanical strength test: The test was conducted in accordance with the national standard GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics".

[0065] Ionic conductivity testing: AC impedance spectroscopy was used, with a test frequency range of 10 Hz. -1 -10 6 Hz, test temperature is 25℃.

[0066] The above embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention shall fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a sulfide electrolyte powder, characterized in that, Includes the following steps: Weigh the raw materials according to the formula, the raw materials include sulfide materials and lithium halides, and the amount of lithium halides is 0.5-5 mol% of the total amount of the sulfide materials and the lithium halides. The weighed raw material is placed in a ball mill jar under an inert atmosphere and ball milled to obtain pretreated powder. The ball milling time is 2-4 hours and the ball milling speed is 300-400 r / min. The pretreated powder is placed in a sand mill under an argon atmosphere for sand milling to obtain a sand mill slurry. The sand milling time is 2-4 hours, the sand milling temperature is controlled below 25℃, and the sand milling linear speed is 11-13m / s. The sand-milled slurry is separated and dried to obtain electrolyte powder. The drying temperature is 50-60℃ and the drying time is 8-12 hours.

2. The preparation method according to claim 1, characterized in that, The sulfide material is Li6PS5Cl, and the amount of lithium halide is 0.5 mol of the total amount of the sulfide material and the lithium halide.

3. The preparation method according to claim 2, characterized in that, The lithium halide is selected from LiCl.

4. The preparation method according to claim 3, characterized in that, The sulfide material is a mixture of Li2S and P2S5, with a molar ratio of Li2S to P2S5 of 3:

1. The amount of lithium halide used is 5 mol of the total amount of the sulfide material and the lithium halide.

5. The preparation method according to claim 4, characterized in that, The lithium halide is selected from LiI.

6. The preparation method according to claim 5, characterized in that, The grinding temperature should be controlled below 20℃.

7. The preparation method according to any one of claims 1 to 6, characterized in that, The ball milling media consists of zirconia balls with a diameter of 5-10 mm, while the sand milling media consists of zirconia beads with a diameter of 0.3-0.8 mm.

8. The preparation method according to claim 1, characterized in that, The purity of the sulfide material is greater than or equal to 99.9%.

9. A method for forming sulfide electrolyte powder, characterized in that, Using the sulfide electrolyte powder obtained by the preparation method according to any one of claims 1 to 8 as raw material, the electrolyte powder is prepared into a film or sheet by cold isostatic pressing to obtain a sulfide electrolyte profile. The cold isostatic pressing pressure is 550-650 MPa and the holding time is 10-15 minutes.

10. The molding method as described in claim 9, characterized in that, It also includes the following steps: The sulfide electrolyte profile is subjected to low-temperature sintering at a temperature of 200-250°C for 1-2 hours. The sintered profiles are then annealed at a temperature of 100-150℃ for 1-2 hours.

Citation Information

Patent Citations

  • Lamp

    CA103775A

  • Composite chemical barrier fabric

    CA1314803C